EP.FRI.5 Defining measurable data points for Emergency Surgical care. (28th October 2021) - Pearson, Katherine; Kowalska, Aleksandra; Jannoo, Shalaina; Bailey, Ian; Elberm, Hassan; Berry, David
Abstract: Aims: Service provision and assessing the impact of future innovations can best be assessed by accurate data collection. Methods: We have devised a simple dataset and implemented prospective data collection detailing patient referral source and outcome (consecutive days from 19.08.20 to 06.01.21) of Acute Surgical admissions. Results: 2706 patient episodes. Conclusions: These baseline figures demonstrate referral source and outcomes. Traditional Emergency Department referrals via the Surgical Registrar result in a noticeable difference in admission rates compared with novel pathways such as ASU Direct which allows admission from ED without discussion. These data are essential to facilitate proper evaluation of service delivery, the impact of novel pathways and would allow units to compare / combine results.